PEMBELAJARAN MENULIS TEKS EKSPOSISI MELALUI THINK TALK WRITE (TTW) PADA SISWA KELAS VIII - Siti Syifa Alfuaodzah (IKIP Siliwangi, 2020)
The enactment of the 2013 curriculum requires the active role of students in producing various types of texts, including exposition texts. The lack of students' ability to express their thoughts makes it difficult for students to produce exposition texts. This research focuses on two problems, namely: (1) how is the implementation of learning to write exposition text through Think Talk Write (TTW) in class VIII students? (2) what is the ability of Grade VIII students in writing exposition text through TTW? The research aims to describe: (1) the implementation of learning to write exposition text through TTW in class VIII students, (2) the ability of class VIII students in writing exposition text through TTW. Qualitative descriptive methods are used in research and utilize interviews, observations, and tests as research techniques. The research results show that (1) the implementation of TTW used by teachers has been carried out in accordance with the syntax of the learning model, namely by applying the think, talk, and write stages. (2) Students' writing ability is classified into good criteria with a percentage of 74%.